2020
DOI: 10.3389/fbioe.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Cationic Macromolecules Highly Effective Against Multi-Drug Resistant Gram-Positive Bacteria and Fungi With No Detectable Resistance

Abstract: The ever increasing threats of Gram-positive superbugs such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Staphylococcus aureus (VRSA), and vancomycin-resistant Enterococccus faecium (VRE) are serious matter of concern worldwide toward public health. Such pathogens cause repeated recurrence of infections through the formation of biofilms which consist of metabolically inactive or slow growing dormant bacterial population in vast majority. Concurrently, dispersal of biofilms origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…It should be noted that cases are rarely reported in the literature in which bactericidal behaviors of cationic materials towards various bacterial species lasted up to 24 h. Indeed, for cationic polymers, dendrimers and peptides, time-kill experiments up to 6 or 8 h of exposure have often been reported [ 58 , 59 , 60 ]. Furthermore, when for cationic bactericidal peptides, such as colistin [ 61 ] and dendrimers [ 28 ], the data are reported at 24 h; it can be observed that, while a rapid killing occurred even after only 5 min [ 61 ], and 1 h [ 28 ] from the contact with the cationic antibacterial device, on the contrary, after 24 h of action, an abundant bacterial regrowth happened.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that cases are rarely reported in the literature in which bactericidal behaviors of cationic materials towards various bacterial species lasted up to 24 h. Indeed, for cationic polymers, dendrimers and peptides, time-kill experiments up to 6 or 8 h of exposure have often been reported [ 58 , 59 , 60 ]. Furthermore, when for cationic bactericidal peptides, such as colistin [ 61 ] and dendrimers [ 28 ], the data are reported at 24 h; it can be observed that, while a rapid killing occurred even after only 5 min [ 61 ], and 1 h [ 28 ] from the contact with the cationic antibacterial device, on the contrary, after 24 h of action, an abundant bacterial regrowth happened.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, cases in which the bactericidal behaviors of cationic materials last up to 24 h are rarely reported in the literature. Commonly, for cationic antibacterial molecules, time-kill experiments are often not reported for more than 2, 4, 6, or 8 h [43][44][45]. In fact, for cationic bactericidal peptides, such as colistin [46] and dendrimers [24], for which data have been reported at 24 h, although rapid killing occurred even after just 5 min [46] and 1 h [24] after contact with the antibacterial device, an abundant bacterial regrowth arose after 24 h of action.…”
Section: Time-kill Curvesmentioning
confidence: 99%
“…In this context, our group introduced a series of amphiphilic cationic macromolecules (ACMs) by functionalizing 600 Da BPEI. [ 265 ] ACMs were synthesized via three simple synthetic steps involving Eschweiler–Clarke methylation followed by quaternization with activated long alkyl group or alkyl ester and amide. Based on structure activity relationship, ACM‐A Hex ( MA‐3 ) (consisting hexyl amide) was identified as the optimum macromolecule which displayed an appreciable antibacterial activity against a panel of MDR Gram‐positive bacteria and fungi including their clinical isolates.…”
Section: Resensitization Of Obsolete Antibiotics By Macromolecular/polymeric Adjuvantsmentioning
confidence: 99%
“…[ 276 ] Also, the antifungal activity of the cationic polymers are less documented in literature. [ 94,123,265,277,278 ] Typically, developing an antifungal agents is a tough challenge as fungal cells are eukaryotic in nature. [ 279 ] Therefore, in cellular level they closely resemble to other eukaryotic species such as mammalian and plant cells, resulting in the poor selectivity of the conventional drugs.…”
Section: Conclusion and Future Aspectmentioning
confidence: 99%